Financial Failure Risk Estimation Of Businesses Listed in BIST Wood Paper Printing Index (Third Sector Social Economic Review, 2026)
Financial distress is defined as the inability of a business to meet its financial obligations on time. Financial distress can be prevented if detected in a timely manner and preventative measures are taken. Numerous models exist in the literature that measure the risk of financial distress. This study aimed to analyze the financial distress risk of companies listed on the Wood Paper Printing Index (XKAGT), which are traded on the Borsa Istanbul. The analysis period for the study was determined as 2020-2024. The study sample consisted of 11 companies with complete annual data available during the analysis period. The Altman Z, Springate S, Zmijewski X, and Grover G models, which are frequently used in the literature, were used in the study. The study findings indicated that five companies were in the financial distress zone in the Altman Z model, eight in the Springate S model, two in the Zmijewski X model, and three in the Grover G model. While two companies were in the safe zone in all models, two companies were in the financial distress zone in all models. Overall, the findings indicate that the Springate S model had the highest number of failed businesses, while the Zmijewski X model had the lowest. Furthermore, no significant changes in scores were observed during the Covid-19 pandemic period covered by the analysis. This study conducted a multidimensional analysis to assess the risk of financial failure in the Forest Paper Printing industry. The study findings provide valuable information for stakeholders and investors operating in the sector.
Keywords: Financial Distress; Altman Z; Springate S; Grover G; Zmijewski X